Determinants of Personal Financial Management in Generation Z: Financial Literacy as a Moderator - Arianti, Novi; Fitriyah, Fitriyah (JMK (Jurnal Manajemen dan Kewirausahaan), 2024)
The management of personal finances among youth has become increasingly important due to changes in contemporary lifestyles. This study thoroughly examines the influences of a hedonism lifestyle, frugal living, and family financial education on personal financial management, with financial literacy serving as a moderating variable among Generation Z students at public universities in Malang City. Through the application of a quantitative methodology, data were amassed via the distribution of questionnaires to the collegiate populace. The data scrutiny was executed employing Structural Equation Modeling (SEM) via SmartPLS version 4 on a sample of 135 participants. The results indicate that a hedonism lifestyle exerts a negative yet statistically insignificant influence on personal financial management, whereas frugal living and family financial education demonstrate a significant positive impact. Financial literacy fails to function as an effective moderator in the relationships between hedonism lifestyle, frugal living, and family financial education concerning personal financial management. These findings highlight the imperative for the formulation of more comprehensive financial education programs aimed at empowering students to enhance their financial management proficiencies.